Role of Aders and OXA23 Genes among Imipenem Resistant Acinetobacter baumannii Isolates from Two Hospitals of Tehran, Iran - Helia Ostad Asadolah-Malayeri; Mojdeh Hakemi-Vala; Kambiz Davari (Iranian Society of Pathology, 2016)
Background: This study aimed to evaluate the role of efflux pump regulator and OXA-23 genes in imipenem resistance Acinetobacter baumannii strains isolated from hospitalized patients in Tehran, Iran. Methods: This study was conducted on 60 A. baumannii isolates collected from patients admitted to the Shahid Motahari and Taleghani Hospitals in Tehran during 2013-14. Antibiotic susceptibility tests (AST) and minimal inhibitory concentration (MIC) was determined by broth micro dilution methods according to CLSI 2014 guidelines. The frequency of efflux pump adeRS and OXA-23 genes were detected by PCR and further sequencing. Results: The resistance of A. baumannii isolates to tested antibiotics was 100% to cefotaxime, ceftazidime, ceftriaxone, ciprofloxacin, cefepime, piperacillin, meropenem, co-trimoxazole and piperacillin/tazobactam, 97% to imipenem, 94% to gentamicin, 83% to amikacin, 76% to tetracycline, and 0.0% to colistin. The MIC of   58 (96.6%) strains to imipenem was highly decreased in the presence of efflux pump inhibitor (PaβN), by 4 to 64 folds. The adeR and adeS genes were detected in 36 (60%) and 59 (98.3%), respectively and the frequency of OXA-23 gene was 57 (95%) of isolates. Conclusion: Existence of adeRS and OXA-23 genes in more than 50% of A. baumannii isolates in this study shows the presumptiverole of efflux pump in simultaneous of carbapenemase production. Therefore, using new strategies are required in order to stop the vertical or horizontal exchanges mentioned genes from the resistant A. baumannii isolates to sensitive strains.